Carpal tunnel syndrome - Kiliç, Bülent; Yücel, Ali Serdar; Yaman, Çetin; Çatikkas, Fatih; Hergüner, Gülten (American-Eurasian Network for Scientific Information, 2015)
Carpal tunnel syndrome is the most common periphery nerve-trapping syndrome. CTS (Carpal Tunnel Syndrome) surgery is the most often operation around the world. Carpal tunnel syndrome occurs as a result of nerve compression at wrist level and generally appears with affective and motor findings. This symptom is also called hand acroparesthesia, tenar palsy, tardy median palsy, median neuritis, median tenar neuritis and so on. It is seen more in adult females over the age of 40. First symptoms are generally burn up, hyperkinesia, weakness, pain, pins and needles, or loss of sense that occur in the area where median nerve is eligible for bilateral spread on hand. Neuronal conduction and electrodiagnostic examinations including needle electromyography are the most common auxiliary methods used for diagnosis. Treatment procedures are generally divided into two, being conservative and surgery. Most commonly applied method is open surgical release. In our study, we shared the perfect results obtained from 186 patients with carpal tunnel syndrome whom we applied surgery under local anesthesia without admission to the hospital and we followed up from outpatient clinics. We also showed that with a practical method as we applied, patients could return their social and work lives within a short period of time. © 2015 AENSI Publisher All rights reserved.
Keywords: Carpal; Conservative treatment; Surgical treatment; Syndrome; Tunnel